ANALISIS PEMASARAN JAGUNG DI KECAMATAN LENTENG KABUPATEN SUMENEP - Moh Fauzi; Bambang Siswadi; Masyhuri Mahfudz (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
Abstract The research objective was to determine the corn marketing channel and the efficiency of corn marketing in Lenteng District, Sumenenp Regency. The data analysis method used is qualitative analysis and quantitative analysis which consists of three approaches namely (a) Marketing Margin (b) Market Integration and (c) Price Transmission Elasticity. The results of qualitative data analysis explain that there are two marketing channels, namely Channel I: Farmers, Brokers, Collector Traders, Consumers. Channel II: Farmers, Middlemen, Collectors, Wholesalers. Marketing functions carried out by farmers: sales. Middlemen: purchases, weighing, loading and unloading, transportation and sales. Collectors: purchases, weighing, loading and unloading, transportation, packaging, depreciation, retribution and sales. Wholesalers: purchasing, weighing, loading and unloading, transportation, depreciation or sorting, levies and sales. The results of quantitative data analysis indicate that the market structure leads to the monopsony market, this can be seen from the transmission price elasticity (η) of 0.56. Keyword : efficiency of marketing, corn, line of marketing